Dose-dependent dual effects of HDAC inhibitors on glial inflammatory response - Samantha Mancino; Mariaserena Boraso; Andrea Galmozzi; Melania Maria Serafini; Emma De Fabiani; Maurizio Crestani; Barbara Viviani (Scientific Reports)
Abstract Neuroinflammation is defined as a process that includes cellular responses designed to protect the central nervous system from external influences, and it initiates in cases of extreme deviations from homeostasis. While it serves a protective role, excessive immune activation can lead to the release of neurotoxic factors, worsening disease progression. Histone deacetylases (HDACs) have been shown to modulate the expression of inflammatory genes by remodeling chromatin through the process of histone deacetylation. HDAC inhibitors (HDACi) alter histone acetylation and affect the transcription of genes involved in inflammatory pathways, making them promising therapeutic tools for the modulation of a variety of inflammatory diseases. However, their use is limited due to non-specific targeting and contradictory results. This study aimed to reconcile conflicting results and share insights on relevant HDACi in the inflammatory response induced by lipopolysaccharide (LPS), considering different exposure scenarios, cellular models, and associated molecular pathways. Specifically, the study evaluated the dose-dependent effects of two broad-spectrum HDACi, Trichostatin A (TSA) and Suberoylanilide Hydroxamic Acid (SAHA, Vorinostat), alongside selective inhibitors—MS-275 (Entinostat, class I), and MC1568 (class II)—on the expression and release of pro- and anti-inflammatory cytokines. Broad-spectrum HDAC inhibitors TSA and SAHA exhibited dose-dependent modulation of LPS-induced cytokine release. Co-treatment with TSA and LPS enhanced pro-inflammatory cytokines (TNF-α, IL-1β) and decreased IL10 in a dose-dependent manner at lower doses (≤ 10 nM), while high concentrations (100 nM) induced the anti-inflammatory IL-10. Pre-treatment with TSA led to a reduction in TNF-α levels induced by LPS, without affecting IL-1β or IL-10 levels. In contrast, the presence of TSA in LPS-triggered alveolar macrophages resulted in a decline in the production of both pro- and anti-inflammatory cytokine, irrespective of the TSA concentration. SAHA exhibited dual effects, enhancing TNF-α and IL-1β at nanomolar levels but suppressing TNF-α at micromolar doses in co-treated glial cells with LPS. Class-selective inhibitors highlighted distinct HDAC roles on LPS modulation: MS-275 reduced, while MC1568 enhanced, TNF-α release, alongside varied IL-1β and IL-10 modulation. To better understand the dual effects of SAHA, transcriptomic analysis of glial cells was conducted in the presence of LPS and low and high SAHA concentrations (100 nM or 5 µM). This analysis revealed a dose-dependent alteration in gene expression and pathway enrichment associated with cytokine signaling and immune regulation (e.g., JAK-STAT). Altogether, these findings reveal insights on the subtle, dose- and context-dependent role of HDACi in modulating glia inflammation.